PENGARUH KOMPETENSI, DISIPLIN KERJA DAN KOMPENSASI TERHADAP KEPUASAN KERJA KARYAWAN TOKO KERSIK PUTIH BEKASI - Febby Ema Yolanda Tarigan (2022)
Toko Kersik Putih is a retail business sector that sells daily needs. This research is a quantitative that aims to determine the influence competence, work discipline and compensation on job satisfaction at Toko Kersik Putih Bekasi. The sample used in this study were all employees of the Toko Kersik Putih amounting to 35 employees. Data collection by questionnaire. The data analysis technique used is descriptive analysis and inferential analysis with the analysis tool used is PLS (Partial Least Square). The results of the test obtained (1) competence has a significant positive effect on job satisfaction, (2) work discipline has no significant effect on job satisfaction, (3) compensation has a significant positive effect on job satisfaction, (4) competence, work discipline and compensation simultaneously have an effect on job satisfaction